Fracture resistance of the permanent restorations for endodontically treated premolars - Lin, Galvin Sim Siang; Ghani, Nik Rozainah Nik Abdul; Noorani, Tahir Yusuf; Ismail, Noor Huda (European Journal of General Dentistry, 2018)
Aim: This study aims to compare the fracture strength, fracture pattern, types of fracture involved, and areas of fractured restoration among endodontically treated permanent lower premolars restored with different restorative materials. Materials and Methods: Sixty-nine mature human permanent lower premolars recently extracted for orthodontic, periodontal, or other reasons were selected and divided into three groups (n = 23). Groups 1 and 2 were endodontically treated. Standardized mesio-occlusal distal cavities were then prepared in both Groups 1 and 2. Groups 1 and 2 were restored with amalgam using Nayyar’s core technique and glass fiber post with composite resin core, respectively. Group 3 consisted of intact teeth which acted as control group. All teeth were tested under constant occlusal load until fracture occurred using a Universal Testing Machine. Data analysis was carried out using Kruskal–Wallis test complemented by Mann–Whitney test. Results: The mean values of fracture strength were 388.05 N (± 158.09) for Group 1, 588.90 N (± 151.33) for Group 2, and 803.05 N (± 182.23) for Group 3. Kruskal–Wallis test showed significant differences among all three groups in terms of fracture strength. The mean load required to fracture intact teeth in Group 3 was significantly highest, followed by Group 2 (P < 0.01) and finally Group 1 (P < 0.01). Most fractures occurred within the coronal structure and were considered favorable pattern. Besides, majority of the fractures occurred on restorations and particularly at the distal side. Conclusions: Teeth restored with fiber post and composite core resulted in higher fracture resistance than teeth restored with Nayyar’s core amalgam restoration.
Keywords: Fracture pattern; fracture resistance; glass fiber post; Nayyar’s core; post and core technique